An analysis of genetic differentiation and geographical variation of spinach germplasm using SSR markers. Issue 2 (August 2014) - Kuwahara, Kouhei; Suzuki, Reimi; Ito, Yusuke; Mikami, Tetsuo; Onodera, Yasuyuki
<x content-type="archive" xml:space="preserve">Abstract</x> To assess the genetic diversity of spinach germplasm, 250 individuals of 50 accessions collected from geographically diverse regions (West Asia, East Asia, Japan, Europe and the USA) were analysed using simple sequence repeat (SSR) markers. A total of 39 polymorphic alleles were identified, with an average of 6.5 alleles per locus for six loci. The overall gene diversity (0.62) in the entire set of individuals suggests that the germplasm has high genetic variability. The West Asian accessions showed the highest gene diversity, with a value of 0.57, followed by the East Asian accessions. These results help confirm the notion that spinach originated from West Asia. Hierarchical analysis of molecular variance revealed significant genetic differentiation among the geographical regions, which accounts for 26% of the total variation detected. Furthermore, pairwise Φst values indicate low genetic differentiation between the East Asian and Japanese germplasm accessions, both of which showed high genetic differentiation from the European accessions. The differentiation between the East Asian and European gene pools may be attributed to the founder effect associated with crop dissemination, as well as to the selection and genetic drift that occurred during the breeding process.